Differences in stroke risk and cardiovascular mortality for Aboriginal and other Australian patients with atrial fibrillation. Issue 5 (6th February 2020) - Nedkoff, Lee; Kelty, Erin A; Hung, Joseph; Thompson, Sandra C; Katzenellenbogen, Judith M
Abstract: Objectives: To assess the risks of stroke and cardiovascular mortality for Aboriginal and non‐Aboriginal Australians with atrial fibrillation. Design: Retrospective data linkage cohort study. Setting, participants: All people aged 20–84 years hospitalised with atrial fibrillation in Western Australia during 2000–2012. Main outcome measures: Stroke incidence rates and mortality after hospitalisation for atrial fibrillation, and 10‐year risks of stroke and of cardiovascular and all‐cause mortality. Results: Among 55 482 index admissions with atrial fibrillation, 7.7% of 20–59‐year‐old patients and 1.3% of 60–84‐year‐old patients were Aboriginal Australians. A larger proportion of Aboriginal patients aged 20–59 years had CHA2 DS2 ‐VASc scores of 2 or more (59.8% v 21.8%). In 20–59‐year‐old Aboriginal patients, the incidence during follow‐up (maximum, 10 years; median, 7.1 years) of stroke (incidence rate ratio [IRR], 3.2; 95% CI, 2.5–4.1) and fatal stroke (IRR, 5.7; 95% CI, 3.9–8.9) were markedly higher than for non‐Aboriginal patients. Stroke incidence was higher for 60–84‐year‐old patients, but the difference between Aboriginal and non‐Aboriginal patients was smaller (IRR, 1.6; 95% CI, 1.3–2.0). Cardiovascular mortality during follow‐up was also higher for 20–59‐year‐old Aboriginal patients (IRR, 4.4; 95% CI, 4.3–5.9). The hazards of stroke (adjusted HR [aHR], 1.67; 95% CI, 1.22–2.28) and cardiovascular mortality (aHR, 1.47; 95% CI, 1.18–1.83) in younger Aboriginal patients remained significantly higher after multivariable adjustment; age/sex, principal diagnosis of atrial fibrillation, and CHA2 DS2 ‐VASc score were the most influential factors. Conclusion: Stroke risk and cardiovascular mortality are markedly higher for Aboriginal than non‐Aboriginal patients with atrial fibrillation, particularly for patients under 60. Strategies for providing evidence‐based therapies and cardiovascular prevention to Aboriginal people with atrial fibrillation must be improved.